Effect of guar gum with glycerol coating on the properties and oil absorption of fried potato chips. (March 2016) - Yu, Lin; Li, Jinwei; Ding, Shaodong; Hang, Feng; Fan, Liuping
Abstract: Effects of guar gum with glycerol coating on the oil absorption of fried potato chips were investigated using dye oil methods, confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). The results showed that coating with guar gum and glycerol could effectively hinder the oil absorption of fried potato chips and have no negative effects on its breaking force. Compared with control or samples coated with guar gum, potato chips with guar gum and glycerol produced a reduction of oil absorption by 51.8% and 34.8%, respectively. Both for control or coated potato chips, penetrated surface oil (PSOs) was dominant in total oil (TOs), followed by structural oil (STOs) and surface oil (SOs). Coating treatment with guar gum and glycerol could significantly reduce the SOs and PSOs of potato chips (P < 0.05). PSOs was the main factor which attributed to the TOs reduction of fried potato chips after coating. CLSM photographs revealed the oil distribution pattern for control or coated sample, and confirmed that PSOs obviously reduced after coating with guar gum and glycerol, followed by SOs. SEM photographs indicated that guar gum, guar gum and glycerol coatings were effective in preventing oil penetration into the potato tissue during frying process. Coating formulations not only enhance the barrier properties of fried potato chips, but also avoid pores and cracks in the fried products with higher toughness. Graphical abstract: Highlights: Coating with guar gum and glycerol hindered the oil absorption of fried potato chips. Coating with guar gum and glycerol has no negative effects on the breaking force. Penetrated surface oil was the main factor which attributed to total oil reduction. Confocal laser scanning microscopy (CLSM) could be used to reveal oil distribution.